Acrylamide in food: Occurrence, metabolism, molecular toxicity mechanism and detoxification by phytochemicals. (May 2023) - Yan, Fangfang; Wang, Li; Zhao, Li; Wang, Chengming; Lu, Qun; Liu, Rui
Abstract: Acrylamide (ACR) is a common pollutant formed during food thermal processing such as frying, baking and roasting. ACR and its metabolites can cause various negative effects on organisms. To date, there have been some reviews summarizing the formation, absorption, detection and prevention of ACR, but there is no systematic summary on the mechanism of ACR-induced toxicity. In the past five years, the molecular mechanism for ACR-induced toxicity has been further explored and the detoxification of ACR by phytochemicals has been partly achieved. This review summarizes the ACR level in foods and its metabolic pathways, as well as highlights the mechanisms underlying ACR-induced toxicity and ACR detoxification by phytochemicals. It appears that oxidative stress, inflammation, apoptosis, autophagy, biochemical metabolism and gut microbiota disturbance are involved in various ACR-induced toxicities. In addition, the effects and possible action mechanisms of phytochemicals, including polyphenols, quinones, alkaloids, terpenoids, as well as vitamins and their analogs on ACR-induced toxicities are also discussed. This review provides potential therapeutic targets and strategies for addressing various ACR-induced toxicities in the future. Graphical abstract: Image 1 Highlights: The acrylamide level in foods and its new metabolites in the body were summarized. The molecular mechanism for acrylamide-induced toxicity was updated. AcRylamide detoxification by phytochemicals was reviewed.